PO14 | Searching for safer rescue immunosuppressive therapy protocols in acquired hemophilia A: two case reports (Bleeding, Thrombosis and Vascular Biology, 2025)
Background: Eradication of autoantibodies (inhibitors) against Factor VIII (FVIII) by immunosuppressive therapy (IST) is a cornerstone of treatment of acquired hemophilia A (AHA). First-line IST usually relies on corticosteroids, while cyclophosphamide or rituximab are used/combined as rescue treatment. IST is associated with significant risk of adverse events, in particular infections/sepsis. We describe 2 cases of successful alternative rescue IST, aimed at minimizing toxicity in very elderly patients.